Improving Service Quality of Rusunawa Implementation Program in Kudus - Septiana Pancawati; Bambang Supriyono; Mardiyono Mardiyono (Wacana Journal of Social and Humanity Studies, 2013)
Development of housing and settlements are still faced the main problems as follows: the limited supply of homes, inadequate housing that is not supported by infrastructure, environmental facilities and public utilities, as well as the growing slums widespread. Government issues Rusunawa Implementation Program to overcome those problems. However some problems arose in its implementation, such as poor environmental condition, poor building quality, inadequate infrastructure and public services. The objectives of the research are to describe, to analyze, and to interpret things as follows: (1) The management of Rusunawa implementation program in order to improve service quality, (2) Improving service quality of Rusunawa program by the authorities. This research used qualitative method with descriptive approach. Information can be obtained byinterview stakeholders, field observations and documentation. From research findings, there are some records that should be highlighted as follows: (1) Rusunawa construction and its supervision influence the building quality. Low performance of those service providers will result in low building quality and vice versa. (2) Rent arrears are higher, an indication of dissatisfaction Rusunawa residents during they stay there. Keywords: Rusunawa, building condition, service quality